Organic compost and irrigation on weight and protein content of Pereskia aculeata leaves - Andrade, Reginaldo Rodrigues de; Galbiatti, João Antônio; Queiroz, Carla Regina Amorim dos Anjos; Pavani, Luiz Carlos (Revista Agrogeoambiental, 2019)
The Pereskia aculeata Mill. plant, known in Brazil as Ora-pro-nobis, is a non-conventional vegetable with high leaf protein content, however studies on the crop system of this leaf vegetable are scarce. Therefore, the objective of the present work was to evaluate the effect of organic compost (OC) rates and irrigation depths (ID) on leaf dry weight (LDW) and leaf protein content (LPC) for P. aculeata plants. The experiment consisted of five OC rates (0, 15%, 30%, 45%, and 60% of the substrate volume) and three ID (50%, 75%, and 100% of the reference evapotranspiration - Et0), with four replications. The analysis of variance by the F test (α = 5% and 1%) and the interpretation of the interaction between the factors by response surface demonstrated the increase of ID from 50% to 100% Et0 is more significant for the increasing in LDW than the increases in OC rates. The highest LDW accumulation was found by combining 33% OC in the substrate with ID of 100% Et0. The lowest LDW resulted from the combination of 60% OC and ID of 50%. The highest LPC was found with the use of 52% OC and ID of 69%, and the lowest with the ID of 100% and absence of OC in the substrate. Keywords: Nutritional supplementation. Waste management. Non-conventional vegetable. Barbados gooseberry. Ora-pro-nobis.